ISOLASI DAN KARAKTERISASI LINAMARASE HASIL ISOLASI DARI UMBI SINGKONG (MANIHOT ESCULENTA CRANTZ) - Askur Rahman (Agroindustrial Technology, University of Trunojoyo Madura, 2010)
The purpose of this research was to know the optimum condition of linamarase enzymatic reaction from bitter cassava. These studies are designed in several stages of interrelated. Starting with the determination of cyanide content of cassava tubers, Isolation andcharacterization linamarase on cassava tuber. The research result showed that linamarase had optimum condition in some activities; pH for about 6, temperature for about 40OC, incubation period for about 3 hours, and Km for about 0.012% and Vmaks for about 0.296 unit.